Relation between motor unit / muscle activity and fine motor performance - Yoshitake, Y. (The Journal of Physical Fitness and Sports Medicine, 2014)
Human movement is a consequence of joint torque or muscle force produced by muscle or muscle groups. Therefore, motor performance in human movements can be determined by the accuracy of joint torque or force produced by muscle/muscle groups. Since motor unit (MU) activity contributes to the force exerted by muscle, the ability to accurately perform steady contractions should be attributed to MU discharge patterns and MU contractile properties. Force fluctuations, which reflect accuracy in fine motor output, can thus affect an individual`s motor control abilities, for example, using chopsticks or going for a walk. Accordingly, mechanistic investigations into the characterization of force fluctuations will provide valuable information concerning the modalities needed to improve or regain motor control in healthy and clinical populations. This paper describes the physiological mechanisms responsible for the adaptation of force fluctuations to various environments. Methodologies for analyzing force fluctuations, particularly in multiple muscle systems, are also addressed to provide additional insights into the mechanisms of fine motor control.